A critical review on relationship of CeO2-based photocatalyst towards mechanistic degradation of organic pollutant. (January 2022) - Fauzi, A.A.; Jalil, A.A.; Hassan, N.S.; Aziz, F.F.A.; Azami, M.S.; Hussain, I.; Saravanan, R.; Vo, D.-V.N.
Abstract: Nanostructured photocatalysts commonly offered opportunities to solve issues scrutinized with the environmental challenges caused by steep population growth and rapid urbanization. This photocatalyst is a controllable characteristic, which can provide humans with a clean and sustainable ecosystem. Over the last decades, one of the current thriving research focuses on visible-light-driven CeO2 -based photocatalysts due to their superior characteristics, including unique fluorite-type structure, rigid framework, and facile reducing oxidizing properties of cerium's tetravalent (Ce 4+ ) and trivalent (Ce 3+ ) valence states. Notwithstanding, owing to its inherent wide energy gap, the solar energy utilization efficiency is low, which limits its application in wastewater treatment. Numerous modifications of CeO2 have been employed to enhance photodegradation performances, such as metals and non-metals doping, adding support materials, and coupling with another semiconductor. Besides, all these doping will form a different heterojunction and show a different way of electron-hole migration. Compared to conventional heterojunction, advanced heterojunction types such as p-n heterojunction, Z–scheme, Schottky junction, and surface plasmon resonance effect exhibit superior performance for degradation owing to their excellent charge carrier separation, and the reaction occurs at a relatively higher redox potential. This review attends to providing deep insights on heterojunction mechanisms and the latest progress on photodegradation of various contaminants in wastewater using CeO2 -based photocatalysts. Hence, making the CeO2 photocatalyst more foresee and promising to further development and research. Graphical abstract: Image 1 Highlights: Recent efforts concerning ceria (CeO2 ) as a single photocatalyst were reviewed. Several strategies modifications of CeO2 -based and heterojunction were reviewed. The modified CeO2 -based photocatalyst exhibits high-performance than pure CeO2 . The modification of CeO2 play a vital role in obtaining desired heterojunction. Several challenges and strategies for development have been proposed.